2011
DOI: 10.1210/jc.2010-3067
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Niacin and Fenofibrate with Lifestyle Changes Improves Dyslipidemia and Hypoadiponectinemia in HIV Patients on Antiretroviral Therapy: Results of “Heart Positive,” a Randomized, Controlled Trial

Abstract: A combination of fenofibrate and niacin with low-saturated-fat D/E is effective and safe in increasing HDL-C, decreasing non-HDL-C and hypertriglyceridemia, and ameliorating hypoadiponectinemia in patients with HIV/ART-associated dyslipidemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
97
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(102 citation statements)
references
References 42 publications
5
97
0
Order By: Relevance
“…Analysis of variance confirmed that the lipid profiles at baseline for the five groups, assigned at random upon enrollment in the Heart Positive Study, were not significantly different. As reported for the entire Heart Positive study 16 treatment with fenofibrate + D&E (Group 3), niacin + D&E (Group 4) and the combined therapy of fenofibrate + niacin + D&E (Group 5) significantly reduced plasma TG, with median reductions of 35 – 42 %. Treatments including niacin with or without fenofibrate increased median HDL-C by 21 – 24%.…”
Section: Resultssupporting
confidence: 57%
“…Analysis of variance confirmed that the lipid profiles at baseline for the five groups, assigned at random upon enrollment in the Heart Positive Study, were not significantly different. As reported for the entire Heart Positive study 16 treatment with fenofibrate + D&E (Group 3), niacin + D&E (Group 4) and the combined therapy of fenofibrate + niacin + D&E (Group 5) significantly reduced plasma TG, with median reductions of 35 – 42 %. Treatments including niacin with or without fenofibrate increased median HDL-C by 21 – 24%.…”
Section: Resultssupporting
confidence: 57%
“…Thirteen of the 20 included studies (65%) assessed cardiorespiratory outcomes [2631, 33, 37, 38, 41, 43, 44, 49]. Sixteen studies (80%) assessed strength outcomes [27–29, 31–33, 3539, 41–44, 49].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies (25%) had low risk for detection bias because authors reported that outcome assessors were blinded to group allocation [2628, 31, 32] (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Niacin is known to control lipoprotein metabolism and suppress synthesis of TG and patients treated with low-fat diet, exercise and niacin had significantly increased plasma concentrations of HDL-C and TC compared to the controls after 24 weeks [146,147]. However, niacin appeared to increase the risk of insulin resistance in HIV patients [146].…”
Section: Nutritional Therapymentioning
confidence: 99%